Analisa keperluan employee assistance program (EAP) bagi guru-guru sekolah menengah di bahagian Betong, Sarawak - Maria, Lok. (Universiti Malaysia Sarawak, UNIMAS, 2006)
The main objective of this study is to develop an Employee Assistance Program (EAP) intervention model for teachers in Betong secondary schools at Sarawak. This study identified secondary schools of Betong division in Sarawak teachers and principles and Sarawak Teacher ’s Union (STU) perception towards EAP implementation needs among teachers in the secondary schools at the area of study. This study discusses about nine category of problems face by the secondary schools teachers in the area of study in term of personal and work - related problem. Personal problem discussed is about health, financial, family, spirituality and stress and work - related problem is include a problem with work, career , interpersonal relationship at the work place and work environment. This study is conducted by Employee Need Assessment Inventory (ENAI) questionnaire and interview methodology . S ample of this study is 154 teachers as respondents from five secondary scho ols in the area of study . The five secondary school involve in this study is SMK Datuk Patinggi Kedit (32 responden t ), SMK St. Augustine (29 responden t ), SMK Saratok (32 responden t ), SMK Kalaka (34 responden t ) and SMK Agama Sri Aman (27 responden t ). The me an score analysis find that respondents of this study need an attention from EAP intervention in four major problems which is stress , work , career and work environment problem . According to Crosstab analysis , this study finds that there is an EAP needs dif ferences between responden t with opposite sex and age range differences. Pearson Correlation Coefficient analysis shows that there is a significant relationship between four major problems of financial, spirituality, stress and interpersonal relationship i n the work place with all of the other problems. An interview with schools principle and Sarawak Teacher ’ s Union (STU) find a support from both parties towards the implementations of EAP for secondary schools teachers in Betong, Sarawak. The researcher has suggested the EAP implementation model for secondary schools teachers in Betong, Sarawak. The EAP model suggested by researcher consists of seven elements known as objective , services , EAP practitioner resources , policy and proc edur e , the placement of EAP consultation room , the administration of EAP and the involvement of Sarawak Teacher ’ s Union in EAP intervention .